Kurikulum divisi tarqiyah at-tholabah untuk pengembangan bahasa arab mahasiswa - Naafiah, Lailatun (Maliki Interdisciplinary Journal, 2025)
This study aims to explain the strategy, content of the material, advantages and disadvantages of the Tarqiyah At-Tholabah division for the development of the Arabic language of students. This research uses a qualitative descriptive approach of case study type. Datacollection techniques use observation of Arabic learning activities, interviews with Tarqiyah At-Tholabah division administrators for the 2022/2023 period and documentation. The subject of this study was a student of Arabic Language Education UIN Maulana Malik Ibrahim Malang. The results of this study revealed that the strategies carried out by the Tarqiyah At-Tholabah division for the development of the Arabic language of students are: Adding 5 Arabic mufradat every week, distributing nahwu shorof material every two weeks, distributing islahul lughoh material (error correction) every two weeks, and Arabic video snippets equipped with quiz questions every month which are distributed through the Instagram account of the Student Association of the Arabic Language Education Study Program UIN Malang and whatsapp group. The content of the material distributed by the Tarqiyah At-Tholabah division for the development of the Arabic language of students is: Adding Arabic mufradat and the meaning of Indonesian along with idioms and examples, distributing material nahwu shorof summaries of several books such as Kitab Alfiyah ibn Malik, Imrithi, Jami’ud Durus, Amtsilatut Tasrifiyah, and i’lal, shared Arabic islahul lughoh (error correction) material and the meaning of Indonesian taken from the book Q ul wala taqul juz 2, and shared Arabic video footage with Indonesian subtitles taken from youtube. The advantages and disadvantages of Tarqiyah At-Tholabah division for the development of Arabic Students, the advantages are: Accessibility, Quick reference, Vocabulary enrichment.